Vocabularies of some of the Indian tribes of N. Western America - Townsend, John Kirk, 1809-1851.
Two notebooks (57 pages and 24 pages) inscribed to Peter Stephen Du Ponceau relating to Indian tribes of the Pacific Northwest.
Ornithologist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Du Ponceau, Peter Stephen, -- 1760-1844.; Indians of North America -- Northwest, Pacific -- Languages; Ornithologists